DAMPAK INFORMASI AKUNTANSI DAN NON AKUNTANSI TERHADAP INITIAL RETURN SAHAM PADA PERUSAHAAN YANG MELAKUKAN INITIAL PUBLIC OFFERING DI BURSA EFEK INDONESIA - Saifudin Saifudin; Alisa Meriani (Universitas Islam Sultan Agung (UNISSULA), Faculty of Economics, Department of Accounting, 2017)
This study aims to analyze the influence of accounting and non-accounting information of the Initial Return company shares Initial Public Offering (IPO). This study uses secondary data by taking a sample of companies that do an IPO on the Stock Exchange 2009-2012. Variables that are used in this study include the size of the company, earnings per share, price earnings ratio, financial leverage, return on assets, value stock offering, firm age, underwriter reputation, the reputation of the auditor, and the ownership of existing shareholders. The data collection method using purposive sampling and analysis of data with multiple linear regression were processed using SPSS. The results showed that the significant effect on the initial return is the size of the company, earnings per share, price earnings ratio, underwriter reputation, and the value stock offering. While financial leverage, return on assets, the proportion of ownership of existing shareholders, underwriter reputation, and firm age no significant effect on initial returns.